(untitled) (Health Renaissance, 2017)
Background: The term chronic headache is commonly taken as headache lasting for more than three months. It is common in general practice with minimal research on the topic in Nepal. Objective: To sort out the common diagnoses of chronic headache and to study the clinical features and demographic profile of patients presenting with chronic headache. Method: A descriptive cross sectional study was conducted (2012 August to 2013 August) at General Practice outpatients in BP Koirala Institute of Health Sciences, a medical university in eastern Nepal. Approval and ethical clearance was taken from Research Committee and Institutional Ethical Review Board. Descriptive statistical analysis was done. Result: 168 patients constituting 1% of outpatient visits presented due to chronic headache. Mean age was 29.57 years (SD 10.53) and female to male ratio was 3.67. Mean number of days of headache was 19.46 days (SD 4.62). Numerical pain score was reported at 7.1/10 (SD 1.85). The mean duration of presentation was 22 months (SD 11). 40% reported impaired activity of more than one week. Headache was classified as chronic migraine in 20.2%, chronic tension type headache in 16.7%, and chronic daily persistent headache in 11.9%. The diagnosis did not fit into any diagnostic criteria in 51.2% cases. Conclusion: Chronic headache is common in females and young age group. Patients present late despite significant pain scores. Significant proportion is still unclassified. Health Renaissance 2015;13(2): 22-29